Efeito do tratamento com extrato padronizado de ginkgo biloba sobre o controle central da ingestão alimentar de ratos - Pereira, Janilda de Pina [UNIFESP] (2016)
The central nervous system plays an important role in controlling food intake. Among the various areas of the central nervous system participating in the homesotático control of food intake and energy expenditure, hypothalamic brain region is considered the most important. It is known that the hypothalamus there are two main populations of neurons involved in this process: the orexigenic, summarizing the neuropeptides NPY, AgRP and MCH, responsible for the sensation of hunger and appetite suppressants, which synthesize neuropeptides alpha-MSH and CART, responsible by the feeling of satiety. The hypothalamus acts to integrate the neural signals and afferent humoral, to coordinate intake and energy expenditure in response to changes in the energy balance, inhibiting or stimulating ingestion. In addition to hypothalamic peptides, the neurotransmitter serotonin plays an important role in many processes regulated centrally, including an important anorexigenic action. Its synthesis occurs in the raphe nuclei and their release occurs throughout the brain, with particular interest in this study, serotoninergic projections for the regions involved in the regulation of energy balance, such as the paraventricular nucleus and arcuate nucleus of the hypothalamus. In previous studies from our laboratory we observed that EGb administration in obese rats at a dose of 500mg / kg / day for 14 days reduced both food intake and the body weight gain. Additionally, preliminary data, not yet published, have demonstrated that an acute gavage EGb at a dose of 500mg / kg stimulated release of 5-HT in the ventromedial hypothalamus of rats eutrophic. Given the above, this study aimed to evaluate the appetite suppressant effect promoted by EGb previously observed in obese mice, the result of a direct action of the herbal medicine on the hypothalamus. For this purpose, initially we evaluate whether acute gavage with EGb 500 mg / kg modified food intake 1, 4 and 24 hours. We also assess the quantification of mRNA anorectic neuropeptides: POMC, CART; orexigenic neuropeptide: AgRP, NPY addition of 5-HT receptors: 5HT2C, 5HT1A, 5HT1B, 5-HTT and ObRb leptin receptor. And POMC protein quantification, of 5HT1B and 5HT2C receptors in eutrophic rats. The food intake in both groups remained unchanged. We note that an acute gavage EGb at a dose of 500mg / kg increased the quantification of mRNA of anorectic neuropeptides POMC and CART, and 5-HT 5HT2C receptor, the GB Group in relation to C. But did not find differences in protein quantification POMC, 5HT1B and 5HT2C.